169k views
5 votes
Complete the missing value in the solution to the equation.

y-3=2(x-1)
x=-1
I will brain list you

User Andypaxo
by
5.3k points

1 Answer

3 votes

Answer:

y = − 1

Hope this helps!

Explanation:

Alright so this is our equation:

y − 3 = 2 ( x − 1 )

We will substitute:

x = − 1

So now our equation looks like this:

y − 3 = 2 ( −1 − 1 )

Now we will get rid of the parentheses:

y − 3 = − 2 − 2

Solve the left side:

y − 3 = − 4

Now add 3 on both sides to find out what y is:

y − 3 = − 4

+3 +3

Add:

y = − 1

Yay! We found our answer! Nice job everyone!

User Jasica
by
4.6k points